Rancang Bangun Aplikasi Pengelolaan Administrasi Ekspor Menggunakan Administrative Workflow System pada PT. Kelola Mina Laut - Muhammad Nurus Hidayatullah; A. B. Tjandrarini; Endra Rahmawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT. Kelola Mina Laut is a company that engages in seafood industry. This company has been exporting their processed products to several countries in Southeast Asia, America, Australia, Europe, the Middle East, China, Korea, Japan and many other countries in the African region. The export process in this company involving several divisions, marketing departments, export division, and documentation division. The complexity of the export process which accompanied by the many parties that interact in this process often causes delays in the administrative process export, this is caused by: 1) employee who related to export administration processes was on duty outside, 2) supporting documents for export administration process has not been submitted to other involved departments. Based on these problems, it was built a web-based export administrative management application that implements administrative workflow system that is supported by push notification techniques such as SMS Gateway to handle the existing problems.